Why are the younger generation anti-political?: critical discourse analysis on political education for beginners - Saherimiko, Saherimiko; Patriani, Ira; Sihaloho, Nahot Tua Parlindungan; Martinus, Martinus; Nge, Herri Junius (Jurnal Konseling dan Pendidikan, 2024)
There are numerous ways for the younger generation to participate in politics, but there are evidence that they are unwilling to join (anti-politics). This study tries to expose two things: (1) the causes of this trend, and (2) remedies to support smooth political circulation in Indonesia as a democratic country. This study accomplishes this purpose by employing Fairclough's Critical Discourse Analysis (CDA). Data acquired from the controversial documentary Sexy Killer's netnography on YouTube. This study highlights several significant findings, particularly the ambivalence and conflict between reality and ideals in today's youth and society. They are skeptical of the earnestness and dedication of government leaders elected through a democratic political process. At the same time, people expect government personnel to carry out their responsibilities. The implications of this study's findings are a criticism of the political education model, which has so far prioritized practical factors above theoretical aspects (content, composition, and proportion).